A Woman’s Heart: Improving Uptake and Awareness of Cardiovascular Screening for Middle-Aged Populations - Kazzi B; Shankar B; Elder-Odame P; Tokgözoğlu LS; Sierra-Galan LM; Michos ED (Dove Medical Press, 2023)
Brigitte Kazzi,1 Bairavi Shankar,1 Petal Elder-Odame,2 Lale S Tokgözoğlu,3 Lilia M Sierra-Galan,4 Erin D Michos2 1Department of Medicine, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 2Department of Medicine, Division of Cardiology, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 3Department of Cardiology, Hacettepe University Faculty of Medicine, Ankara, Turkey; 4Cardiology Department of the Cardiovascular Division, American British Cowdray Medical Center, Mexico City, MexicoCorrespondence: Erin D Michos, Medicine and Epidemiology Division of Cardiology, Johns Hopkins University School of Medicine, Baltimore, MD, USA, Tel +1 410 502-6813, Email edonnell@jhmi.eduAbstract: Mid-life, the years leading up to and following the menopause transition, in women is accompanied by a change in cardiometabolic risk factors, including increases in body weight, changes in body composition, a more insulin-resistant state, and a shift towards a more atherogenic dyslipidemia pattern. Cardiovascular disease (CVD) risk assessment should be performed continually throughout the lifespan, as risk is not stagnant and can change throughout the life course. However, mid-life is a particularly important time for a woman to be evaluated for CVD risk so that appropriate preventive strategies can be implemented. Along with assessing traditional risk factors, ascertainment of a reproductive history is an integral part of a comprehensive CVD risk assessment to recognize unique female-specific or female-predominant factors that modify a woman's risk. When there is uncertainty about CVD risk and the net benefit of preventive pharmacotherapy interventions (such as statins), measuring a coronary artery calcium score can help further refine risk and guide shared decision-making. Additionally, there should be heightened sensitivity around identifying signs and symptoms of ischemic heart disease in women, as these may present differently than in men. Ischemia from coronary microvascular disease and/or vasospasm may be present even without obstructive coronary artery disease and is associated with a heightened risk for major cardiovascular events and reduced quality of life. Therefore, correctly identifying CVD in women and implementing preventive and treatment therapies is paramount. Unfortunately, women are underrepresented in cardiovascular clinical trials, and more data are needed about how to best incorporate novel and emerging risk factors into CVD risk assessment. This review outlines an approach to CVD screening and risk assessment in women using several methods, focusing on the middle-aged population.Keywords: women's health, mid-life, risk assessment, cardiovascular disease, prevention, menopause